Creative Applicability of Dunhuang Floral Tiles in Architectural Modern Interior Decoration - Yanda, Du; Suwanthada, Prathabiai (Journal of Ecohumanism, 2025)
Dunhuang art encompasses a variety of art forms. The production of interior furnishings in conjunction with Dunhuang floral tile art through moulding, painting, or carving methods was designed. Local artists’ participants were interviewed and observed while recording data using a camera, video, and group discussion. There are 419 architectural models and mural replicas at the Dunhuang murals, which are ongoing at the Mogao caves’ grottoes in Gansu province. Temples of Dunhuang: Buddhist Art on China’s Silk Road, Dunhuang floral tiles with patterns are unique in shape, novel in conception, rigorous in structure, vivid in the image, and numerous in number and variety as a form of art for demonstrating their intrinsic, deep historical origins and cultural Chinese Buddhist culture. Dunhuang cave art is closely related to Buddhism. Chinese classical religious architecture protects relevant cultural relics, and the creative applicability of Dunhuang floral tiles in modern architectural interior decoration is significant.